1990
DOI: 10.1007/bf01833988
|View full text |Cite
|
Sign up to set email alerts
|

Mean transit time for videodensitometric assessment of myocardial perfusion and the concept of maximal flow ratio: A validation study in the intact dog and a pilot study in man

Abstract: Over the last decade it has become more and more obvious that besides anatomical information about the severity of coronary artery stenoses, information about coronary and myocardial blood flow is necessary to understand the functional significance of these obstructions and to evaluate the result of an intervention. Several methods have been proposed for this purpose, each of these having their particular limitations. In this study a new method is shortly described which allows the accurate calculation of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
13
0
4
Order By: Relevance
“…for the densitometric parameter 'rise time of the quality weighted mean' compared before and after stimulation of coronary flow with papaverin. In [8,10] the alternative way of considering regions of interest only at special locations, together with corresponding windows outside the myocardium for background subtraction, was investigated. The aim was to obtain high quality densograms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…for the densitometric parameter 'rise time of the quality weighted mean' compared before and after stimulation of coronary flow with papaverin. In [8,10] the alternative way of considering regions of interest only at special locations, together with corresponding windows outside the myocardium for background subtraction, was investigated. The aim was to obtain high quality densograms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the time of maximum may jump for a smooth change of a densograrn with two local maxima. Even the fitting of a template function to a densogram [8,10] can behave in an unstable manner in certain constellations and this extends to the resulting parameters. An additional classification is therefore desirable to detect densograms that differ from SSD's by shape or mode of origin (superposition of different perfusion beds, collateral supply, late superposition by opacification of the venous system, etc.).…”
Section: Parameters For Single-and Multi-source Densograms 2231 Stmentioning
confidence: 96%
See 2 more Smart Citations
“…Several previous studies have evaluated coronary blood flow by using angiographic images. Pijls et al (40,41,42) measured the mean transit time for the assessment of myocardial perfusion by videodensitometry. Molloi et al (35,37) have shown that the FPA analysis technique can be used to measure absolute coronary blood flow by analyzing the propagation of a contrast material signal in the coronary system.…”
Section: Protocolmentioning
confidence: 99%